(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
According to Mann and Wainwright, climate change will lead to a reorganisation of the political. There is therefore an urgent need to understand how this will impact the currently dominant power relations: for the two authors, the need to find a balance between human beings and climate will lead to an unprecedented form of planetary sovereignty, which will develop from nation-states along two main dichotomous lines (sovereignty and capitalism). Why, however, is the climatic Leviathan slow to make its appearance and establish its hegemony? Perhaps, it is possible to assume that the climate issue – assuming the role of amplifier of 21st century constitutional tendencies – will prove to be fertile ground for the growth of uncontrolled private power.